Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/jwmg.22360
|View full text |Cite
|
Sign up to set email alerts
|

Sloth bear maternal and resting den locations in eastern Karnataka

Abstract: Sloth bears (Melursus ursinus) use resting and maternal dens. Resting dens are used by both sexes, usually during the mid‐day when sloth bears are least active. Maternal dens are used by female bears to give birth and raise cubs. The purpose of our study was to better understand the denning ecology of sloth bears in eastern Karnataka so that important denning habitat can be delineated and protected. We documented resting and maternal dens from 2014 to 2018 in 5 different study areas surrounded by agriculture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This study used methodology similar to ours and also suggested the potential use of caves as dens by Asiatic black bears to avoid heat and human-caused disturbances (Fahimi et al 2011). In addition to the Asiatic black bear, such behavior has been only sporadically reported in the sloth bear, where the species uses naturally occurring caves or crevices as den sites to avoid heat and predators (Baskaran et al 2015, Swaminathan et al 2023). All of the dens were located between large boulders, which is different from other parts of the species' range but similar to other studies in Iran (Fahimi et al 2011, Kozakai et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used methodology similar to ours and also suggested the potential use of caves as dens by Asiatic black bears to avoid heat and human-caused disturbances (Fahimi et al 2011). In addition to the Asiatic black bear, such behavior has been only sporadically reported in the sloth bear, where the species uses naturally occurring caves or crevices as den sites to avoid heat and predators (Baskaran et al 2015, Swaminathan et al 2023). All of the dens were located between large boulders, which is different from other parts of the species' range but similar to other studies in Iran (Fahimi et al 2011, Kozakai et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Asiatic black bears ( U. thibetanus ), American black bears ( U. americanus ), and brown bears ( U. arctos ) hibernate in dens during winter in the northern parts of their ranges (Penteriani and Melleti 2021). Further, sloth bears use maternal and resting dens (Swaminathan et al 2023). Asiatic black bears hibernate in northern parts of their range but their den-site selection in other regions remains less understood (Fahimi et al 2011).…”
mentioning
confidence: 99%
“…Black bears are a forest-adapted species, so we also predicted the highest densities of black bears would occur in forested vegetation communities that provide cover for thermoregulation and security, in addition to food (Barnes and Bray 1967, Herrero 1972, Sawaya et al 2016. Finally, following principles of the human shield hypothesis, where subordinate animals use humans as cover from dominant animals (Berger 2007, Swaminathan et al 2023, we predicted higher densities of black bears near roads; black bears may use these areas to avoid grizzly bears, which tend to select areas farther from roads Manley 1990, Ladle et al 2018).…”
mentioning
confidence: 98%